One in three or three in one: Integrating three competing theoretical models (TPB, VIP, and PADM) to explain the intentions to act/actions against climate change - Kim, Miri; Kim, Seoyong; Jeon, Sehyeok (Heliyon, 2024)
This study examines multidimensional factors affecting climate change response behavior. It constructs an integrated model based on the theory of planned behavior, value–identity–personal norms model, and protective action decision model, as a single theory cannot capture the complex nature of human behavior. Recent studies have shown that integrating theories include various influencing factors and indicate higher explanatory power. Therefore, this study uses an integrated model to identify multidimensional influencing factors. The fit of the integrated model was confirmed to be excellent (Chi-square = 1271.866, p = .000, GFI = 0.930, NFI = 0.940, RMSEA = 0.060, TLI = 0.937, SRMR = 0.059), and identity exhibited the greatest effect on personal norms, followed by intention on behavior. The integrated model suggests the following path: ecological value → identity → personal norms → stakeholder awareness → intention → behavior and then ecological value → identity → perceived behavioral control → risk awareness → intention → behavior. The results of the integrated model suggest that a multifaceted approach is necessary to promote climate change response behavior. Various factors, such as ecological value, identity, personal norms, stakeholder awareness, perceived behavioral control, and risk awareness, interact and influence behavior. Policies and programs that comprehensively consider these factors should be established.
Keywords: Climate change awareness; Protective action decision model; Response to climate change; Theory of planned behavior; Value–identity–personal norms model